‘Il topo, le piante, i vermi. Giacomo Leopardi, ed Erasmus e Charles Darwin’ - Angioy, A (2017)
My thesis focuses on three apparently distant authors: Giacomo Leopardi, Erasmus Darwin and Charles Darwin. Exploring significant affinities between their view of Nature, and of human and animal existence, the thesis does not ignore chronological discrepancies (Leopardi died in 1837, the year in which Darwin returns from his voyage on the Beagle, and the Origin of Species would be published only in 1859), but rather offers a ‘diffractive’ interpretation that considers Leopardi and Charles Darwin’s shared reading. From an extensive study of Leopardi’s work, one figure clearly emerges: Erasmus Darwin, Charles’s grandfather. Erasmus was a physician, a poet, a free thinker and materialist, a man who dared to write about sexuality and, following in the footsteps of the Roman poet Lucretius, about the nature of things. He was also one of the most important ‘lunar man’, as Jenny Uglow recorded in Lunar Men, who anticipated many evolutionary ideas, a committed campaigner against slavery (as was his grandson Charles, see Adrian Desmond and James Moore’s Darwin’s Sacred Cause). The discovery of a copy of Erasmus Darwin’s bestselling and famous book The Loves of the Plants in the library of Leopardi’s family home in Recanati, provides ‘evidence’ for the evolutionary hints scattered in Leopardi’s works, above all the prose works Zibaldone and Operette morali, and among the poems ‘Paralipomeni alla Batracomiomachia’, ‘I nuovi credenti’, and ‘La Ginestra’. In my study I have therefore adopted a comparative approach in order to shed light on the important points of contact between the formative backgrounds of both Leopardi and Charles Darwin, including first and foremost Erasmus Darwin. As Rebecca Stott pointed out in Darwin’s Ghosts, Erasmus was one of Charles's most important ‘ghosts’ and significant precursor of his work. Employing an interdisciplinary approach, I researched Erasmus Darwin’s works, particularly The Loves of the Plants, but also Zoonomia, comparing his ideas with the works and thoughts of both Charles Darwin and Leopardi. The image of the ‘gnome’ in Leopardi as in Erasmus Darwin appears to be the witness of an Earth wounded by volcanos and natural catastrophes but above all ravaged by human cupidity. Thus I envisaged a triangulation – where Erasmus Darwin is the base of the triangle and Leopardi and Charles Darwin are the catheti. Within this configuration, the thesis explores the transmission of ideas across borders of time and space, and suggests that, within this triangulation, Leopardi can be considered a forerunner of Charles Darwin not only, as many scholars have pointed out, because of his knowledge of Buffon, La Mettrie and others but also because of their shared knowledge of Erasmus’s work. The title of the thesis has been inspired by three books which have been fundamental for my research: L’io del topo by Liana Cellerino who investigated Leopardi's anti-anthropocentrism in his poem ‘Paralipomeni’; The Loves of the Plants, Erasmus Darwin’s poem; and Adam Phillips’s Darwin’s Worms, an analysis of the works of Darwin and Freud. Phillips’s book, especially, has been an important inspiration for my thesis, particularly in the final part dedicated to Leopardi’s last poem ‘La Ginestra’. I read the plant’s resistance to Nature’s harshness as an equivalent to the resilience of worms, the ‘heroes’ of Charles Darwin’s last masterpiece The Formation of Vegetable Mould, published in 1881. Nature in all three writers is shown to be far from idyllic, but all three equally stress how our awareness of what imperils the human condition – as Phillips puts it “we are all relaxing in the killing fields” – can lead to solidarity and resistance.